Complex Regional Pain Syndrome: A Quantitative Review of Current Treatments - Santos, Fernando Furtado; Takahashi, André Akira Ramos; Ponce, André; Franceschini, Paulo Roberto; Aguiar, Paulo Henrique Pires de (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Introduction Complex regional pain syndrome (CRPS) is a disease that causes intense pain mainly in the upper and lower limbs of the patients, impairing the quality of life of those affected by the syndrome. Its pathophysiology has not yet been fully discovered and described. Also, treatments need to advance in the search for pain relief in those affected by the disease. The present article aims to describe the pathophysiology of CRPS and, mainly, to quantitatively analyze the efficiency of new treatments against pain caused by the disease.Methods Several articles on clinical trials described in a table were included in the present study, and a systematic review of the effectiveness of current treatments was performed.Results A total of 29 articles from clinical trials were selected using the preselection criteria. Surgical treatments against CRPS had a 56.9% efficiency in reducing painful sensation, and conservative treatments against CRPS had a 40.82% efficiency in reducing pain sensation.Conclusion Complex regional pain syndrome is a disease that causes pain in patients and worsens the quality of life of those affected by it. The treatments are diverse, and their efficiencies vary from bad to excellent.
Keywords: complex regional pain syndromes; neurosurgery; therapeutics; pathology